2014
DOI: 10.1002/art.38641
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Oxidative Stress Reduce the Response of Human Articular Chondrocytes to Insulin‐like Growth Factor 1 and Osteogenic Protein 1

Abstract: Objective A reduced response of articular chondrocytes to growth factors with aging could contribute to the development of osteoarthritis. The purpose of this study was to determine the effects of aging and oxidative stress on the response of human articular chondrocytes to insulin-like growth factor-1 (IGF-1) and osteogenic protein-1 (OP-1). Methods Chondrocytes isolated from normal human articular cartilage obtained from tissue donors were cultured in alginate beads or monolayer. Cells were stimulated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 33 publications
4
79
0
Order By: Relevance
“…1) (73). Furthermore, recent studies show that oxidative stress can: 1. activate HSP70, a major regulator of chondrocyte homeostasis and inflammation (74); 2. stimulate nuclear protein 1 (Nupr1), involved in gene transcription, which regulates matrix metalloproteinase 13 (MMP-13) expression (75); and 3. increase ERK and p38 phosphorylation (76). These results demonstrate novel regulations of oxidative stress in chondrocytes from articular cartilage.…”
Section: Oxidative Stress Induced In Mature Articular Cartilage By Ramentioning
confidence: 91%
See 1 more Smart Citation
“…1) (73). Furthermore, recent studies show that oxidative stress can: 1. activate HSP70, a major regulator of chondrocyte homeostasis and inflammation (74); 2. stimulate nuclear protein 1 (Nupr1), involved in gene transcription, which regulates matrix metalloproteinase 13 (MMP-13) expression (75); and 3. increase ERK and p38 phosphorylation (76). These results demonstrate novel regulations of oxidative stress in chondrocytes from articular cartilage.…”
Section: Oxidative Stress Induced In Mature Articular Cartilage By Ramentioning
confidence: 91%
“…These results demonstrate novel regulations of oxidative stress in chondrocytes from articular cartilage. Oxidative stress also inhibits IGF-1-stimulated Akt phosphorylation (76) leading to low Akt activation in stressed chondrocytes. These pathways affect many biological processes, including mitosis, apoptosis and angiogenesis (77).…”
Section: Oxidative Stress Induced In Mature Articular Cartilage By Ramentioning
confidence: 98%
“…For these experiments, younger donors were Ͻ50 years old, and older donors were Ն50 years old. The age cut-off for young and old donors was chosen based on a previous study from our group that demonstrated a decline in the response to IGF-1 and altered signaling under conditions of oxidative stress in chondrocytes from donors older than 50 years (27). The average age of younger cartilage was 41.3 Ϯ 6.1 years (range, 36 -48) with a Total Knee Macroscopic Cartilage Score of 57.75 Ϯ 2.8 corresponding to Grade I (minimal changes).…”
Section: Methodsmentioning
confidence: 99%
“…Disrupted pro-anabolic IGF-1 signaling has been implicated in the pathogenesis of OA, and age-associated reductions in the chondrocyte response to IGF-1 have been associated with oxidative stress (26,27). The aim of this study was to examine whether menadione-induced oxidative stress could promote chondrocyte PRX hyperoxidation in an age-related manner and determine whether this was associated with disrupted IGF-1 signaling, chondrocyte cell death, and osteoarthritis.…”
mentioning
confidence: 99%
“…Research has shown that IGF-1 plays an important role in promoting cartilage repairing progress, while OA is mainly characterized by degeneration of cartilage; therefore, increased IGF-1 would help to promote cartilage repair progress [24]. IGF-1 accelerates the differentiation of chondrocytes, stimulates the synthesis of cartilage matrix, and inhibits the matrix decomposition mediated by chondrocytes [25]. IGF-1, its receptor, and IGF-binding proteins together were called as IGF system and act jointly.…”
Section: Discussionmentioning
confidence: 99%